2014
DOI: 10.4171/aihpd/7
|View full text |Cite
|
Sign up to set email alerts
|

Formal multidimensional integrals, stuffed maps, and topological recursion

Abstract: We show that the large N expansion in the multi-trace 1 formal hermitian matrix model is governed by the topological recursion of [EO07a] with initial condition. In terms of a 1d gas of eigenvalues, this model includes -on top of the squared Vandermonde -multilinear interactions of any order between the eigenvalues. In this problem, the initial data pω In particular, by substitution one may consider maps whose elementary cells are themselves maps, for which we propose the name "stuffed maps". In a sense, our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(94 citation statements)
references
References 15 publications
0
91
0
3
Order By: Relevance
“…In [16], we discovered that to study more general Hermitian matrix models, we must introduce the blobs. We also notice a similarity between blobs and nonperturbative effects in matrix models, and this similarity demands further investigation.…”
Section: Topological Recursionmentioning
confidence: 99%
“…In [16], we discovered that to study more general Hermitian matrix models, we must introduce the blobs. We also notice a similarity between blobs and nonperturbative effects in matrix models, and this similarity demands further investigation.…”
Section: Topological Recursionmentioning
confidence: 99%
“…One notices that expanding the logarithm of (3.11) the matrix model one obtains looks like the matrix models introduced in [6] for specific choices of the values of the formal variables. The models introduced therein are studied because of their connection to LMO invariants of 3-manifolds (see [7]).…”
Section: T 4 Tensor Models and Intermediate Field Representationmentioning
confidence: 99%
“…For instance an orthogonal polynomial is provided by P N,t 4 (x) = det(x − M ) . Following [12], changing variables to eigenvalues leads to: 6) where dµ(x) = exp(−N V (x))dx. Then write:…”
Section: Jhep08(2015)129mentioning
confidence: 99%
“…For general r, Borot [23] has shown that the formal asymptotic expansion of the partition function subordinate to multi-particle potentials is captured by a generalisation of the topological recursion. The existence of the all-order asymptotic expansion was established by the authors in [30] under certain regularity assumptions on the multi-particle interactions.…”
Section: Generalisationsmentioning
confidence: 99%
“…For β = 2, with the same precise meaning that was discussed in Section 1.1.2, the N-fold integral: [23], and encompasses a large class of statistical physics models on two-dimensional random lattices. The simplest ones occur for r = 2, and the only other interesting cases we are aware of have r = ∞.…”
Section: Statistical Physics In Two-dimensional Random Latticesmentioning
confidence: 99%